Growth Performance Of Merawangarab Chicken With Different Feed Composition - Sri Darwati; Ilham Rizki; Harini Nurcahya (Journal of Tropical Biodiversity, 2022)
Indonesia has a variety of local chicken famincluding merawang chicken and arabic chicken. Merawang chickens have potential as dual-purpose type chickens and laying types for arabic chickens. Crossing the merawang chicken with arabic chicken is expected to be an alternative to increase the productivity of local Indonesian chickens through increasing the genetic material of local chickens and developing local chickens. Appropriate feed supports livestock productivity performance. This study aimed to examine the growth performance of merawangarab chickens with 50% merawang and 50% arabian genetic composition fed mixed feeds with commercial feed compositions for broilers with different rice bran from the 4th week to the 12th week. The number of DOC used as many as 80 tails and not differentiated by sex, 60% of the feed used; 80%: 100% commercial broiler feed for starter phase mixed with 40% rice bran; 20%; 0%. The study used a Randomized Block Design (RAK) with a hatching period as a group. The variables measured were feed consumption, body weight, feed conversion, and mortality. Feed and drinking water are provided ad libitum. The results showed that the performance of merawangarab chickens with different compositions of commercial feed and rice bran was the same (P>0.05) for all growth variables. The average body weight at 12 weeks of age was 1064.6-1167.8 g. In conclusion, the growth of merawangarab chicken by replacing commercial feed up to 40% with rice bran is still good.